(untitled) (Journal of Information Technologies in Education (ITE), 2015)
This study analyzes opportunities for using cloud technologies in higher education in Ukraine. On the basis of principles of the system approach, it examines the main task of cloud technologies, strategic and tactical goals of cloud computing at the technical universities, as well as problems that arise in their implementation in the educational process. The paper discusses the main trends in the use of cloud technologies in higher technical education, analyzes cloud services used by leading technical universities in Ukraine in management and learning. The typical structure of a Technical University is considered with public, private, and hybrid clouds. The experience of Cherkasy State Technological University in the use of cloud technologies at management and learning is presented. Considerations are particularly given to distance support,mobile, and blending learning, virtualization mechanism to support the students learning at natural, mathematical sciences and engineering through the utilization of individual desktops.